Post-colonial Cameroon politics, economy, and society - Takougang, Joseph; Amin, Julius A. (Lexington Books, 2018)
This book by a diverse group of Cameroonian scholars, both at home and in the diaspora, presents multidisciplinary insights on some of the critical issues including political, economic, and sociocultural developments in post-colonial Cameroon.